American Express from a strategic perspective. - Tan, Wei Li. (2013)
In the recent few years, in a bid to increase income, AmEx has diversified its businesses through prepaid cards, targeting the mass market, engaging small business owners and various social media strategy. While these strategies have been successful in generating record profits for the company, the question remains on whether it is the right long term strategy.